2019
DOI: 10.3390/nu11092096
|View full text |Cite
|
Sign up to set email alerts
|

MTA1-Dependent Anticancer Activity of Gnetin C in Prostate Cancer

Abstract: The overexpression of metastasis-associated protein 1 (MTA1) in prostate cancer (PCa) contributes to tumor aggressiveness and metastasis. We have reported the inhibition of MTA1 by resveratrol and its potent analog pterostilbene in vitro and in vivo. We have demonstrated that pterostilbene treatment blocks the progression of prostatic intraepithelial neoplasia and adenocarcinoma in mouse models by inhibiting MTA1 expression and signaling. In the current study, we investigated the MTA1 targeted anticancer effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The inhibitory effects of resveratrol and pterostilbene on MTA1-mediated angiogenesis involving HIF-1a, VEGF, and IL-1β were also consistently reported (Kai et al, 2011;Li et al, 2013;Dhar et al, 2016;Butt et al, 2017;Hemani et al, 2022). We have also shown the MTA1-mediated and MTA1 independent chemopreventive and therapeutic value of Gnetin C in prostate cancer in vitro and in vivo (Kumar et al, 2019;Gadkari et al, 2020). Importantly, stilbenes can inhibit MTA1-associated oncogenic miRNAs (Figure 3).…”
Section: Stilbenes As Inhibitors Of Mta1 Signaling and Associated Mir...supporting
confidence: 81%
See 2 more Smart Citations
“…The inhibitory effects of resveratrol and pterostilbene on MTA1-mediated angiogenesis involving HIF-1a, VEGF, and IL-1β were also consistently reported (Kai et al, 2011;Li et al, 2013;Dhar et al, 2016;Butt et al, 2017;Hemani et al, 2022). We have also shown the MTA1-mediated and MTA1 independent chemopreventive and therapeutic value of Gnetin C in prostate cancer in vitro and in vivo (Kumar et al, 2019;Gadkari et al, 2020). Importantly, stilbenes can inhibit MTA1-associated oncogenic miRNAs (Figure 3).…”
Section: Stilbenes As Inhibitors Of Mta1 Signaling and Associated Mir...supporting
confidence: 81%
“…Nutritional interception in intermediate- and high-risk active surveillance patients should target specific molecular pathways. Particularly, our group has shown that natural dietary stilbenes exhibit targeted chemoprotective, interceptive and therapeutic effects against prostate cancer in vitro and in vivo ( Kai et al, 2010 ; Li et al, 2013 ; Dhar et al, 2016 ; Butt et al, 2017 ; Kumar et al, 2019 ; Gadkari et al, 2020 ; Levenson, 2020 ; Hemani et al, 2022 ). This review will focus on the potential of natural stilbenes to protect against prostate cancer through the modulation of specific miRNAs that can conceivably be detected in bloodstream and urine and serve as prognostic and predictive biomarkers for certain populations of prostate cancer patients in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the present study indicated its role in predicting recurrence risk of prostate cancer. MTA1 has been reported to drive malignant progression and bone metastasis in prostate cancer in several studies [ 33 , 34 ], whereas the protective effect of TP53 is well-known [ 35 , 36 ]. RORC encoding ROR-γ could induce androgen expression in prostate cancer [ 37 ] and is a potential therapeutic target in castration-resistant prostate cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lundqvist et al [ 213 ] demonstrated, using prostate cancer (LNCaP) and normal prostate (RWPE) epithelial cells, that resveratrol and its analogs inhibited the activation of androgen receptors. Furthermore, Kumar et al [ 214 ] showed in two lines (DU145 and PCM3) of human prostate carcinoma cells that dimer resveratrol gnetin C, which is a natural resveratrol dimer found in melinjo ( Gnetum gnemon L.) seeds [ 215 ], downregulated the metastasis-associated 1 protein (MTA1)-mediated pathway, while promoting the apoptosis and decreasing the aggressiveness of prostate cancer cells. The anti-cancer action mediated by gnetin C turned out to be more potent compared to resveratrol.…”
Section: The Role Of Nutritional Factors and Foodstuffs On Prostatmentioning
confidence: 99%